Food Allergy Management in Georgia K-12 Public Schools: Examining the Role of Demographic Factors, Policies, and Teacher Training - Sparks, Bentley (My University, 2025)
Food allergies pose health risks in schools, making effective management essential for student safety. This study examines the impact of demographics, school policies, and teacher training on food allergy management in Georgia K-12 public schools. Guided by resource deprivation theory and social cognitive theory, this research identifies predictors of teacher knowledge, self-efficacy, and the frequency and treatment of food-induced allergic reactions. Using a survey-based nonexperimental design, data were collected from 536 teachers and 58 school nurses across rural, suburban, and urban schools. Analyses included multiple regression, negative binomial regression, and bootstrap resampling.
Keywords: Health education; Dissertations, Academic--United States; Anaphylaxis; Food allergy; Self-efficacy; Public schools; Teachers--Training of